Can Thin Capitalization And Transfer Pricing Activities Reduce The Tax Burden - Winarto, Winarto; Daito, Apollo (Dinasti International Journal of Economics, Finance & Accounting, 2021)
The purpose of this research is to examine the effect of thin capitalization and transfer pricing as a vehicle for companies to reduce their corporate tax burden. The research method used is a quantitative-explanation, with the proxy of tax avoidance is ETR. This research found that thin capitalization activities and transfer prices have a negative and significant effect on tax avoidance. This research also found that institutional ownership strengthens the effect of thin capitalization and transfer pricing on tax avoidance. This research contributes to the literature on using the PLI ratio, namely ROCE as a measurement tool for transfer pricing activity, which provides a new methodological contribution to tax avoidance research through transfer pricing activities in Indonesia's manufacturing companies. This study proves that Return On Capital Employed can be used as a transfer pricing activity measure.